The Strategy of Promoting the Unionpay in The Global Market: Problems And Solutions - Yue Ji; Alexey Chernov (Communications of International Proceedings, 2021)
The relevance of the study is that China's payment industry has now reached the leading level in the world, especially China's mobile payments industry. As a leading acquirer in the industry, China UnionPay Merchant Services Co., Ltd. has shifted its views to overseas countries, seeking to open up in overseas markets.The purpose of the article is to analyze the current strategy of the UnionPay payment system in the framework of the development of the world market. Within the framework of this goal, the following tasks were solved: 1) the prerequisites for the formation of the national payment system in China were considered, 2) the stages of its creation were highlighted, 3) the achieved result was analyzed. UnionPay is available in most ASEAN countries; the next stage of the company's management is to enter the markets of the CIS countries. The authors also highlighted the key factors that allowed China Union Pay to enter the world top in card issuance: 1) formation in a closed environment with favorable growth of the national economy; 2) system management and building an extensive infrastructure for receiving and serving consumers; 3) fast and successful implementation of innovative technologies; 4) cooperation with competing payment systems to gain experience and convenience of existing customers.
Keywords: payment system; international payments; national payment card system; non-cash payment instruments; payment system problems; "UnionPay" payment card; UnionPay; China.